Effect of Liquidity and Bank Size on the Profitability of Commercial Banks in Bangladesh - Parvin, Shahnaz; Chowdhury, A. N. M. Minhajul Haque; Siddiqua, Ayesha; Ferdous, Jannatul (Asian Business Review, 2019)
Nowadays Modern economy cannot be thought without banks. The banks of Bangladesh have great contributions to the development of this country. This study concentrated on the commercial banks in Bangladesh to determine the effect of liquidity and bank size on the profitability of the banks during the year 2011-2015. Seven commercial banks were selected and descriptive as well as correlations analysis statistics were used to conduct the study. Data from the annual reports of the banks were analyzed. The results stated that loan to asset ratio and bank size had a positive relation with return on asset (ROA) which was the indicator of profitability. The results also showed that deposit to asset ratio had a negative impact on the ROA of the selected banks. Although there were relationships among liquidity, bank size and profitability but liquidity and bank size did not have a significant influence on the profitability of the banks.JEL Classification Code: G 21
Keywords: Commercial banks; liquidity; bank size; return on asset